Emerging applications of multifunctional elastin-like recombinamers. (January 2011) - Rodríguez-Cabello, J Carlos; Martín, Laura; Girotti, Alessandra; García-Arévalo, Carmen; Arias, F Javier; Alonso, Matilde
Elastin-like recombinamers have grown in popularity in the field of protein-inspired biomimetic materials and have found widespread use in biomedical applications. Modern genetic-engineering techniques have allowed the design of multifunctional materials with an extraordinary control over their architecture and physicochemical properties, such as stimuli-responsiveness, monodispersity, biocompatibility or self-assembly, amongst others. Indeed, these materials are playing an increasingly important role in a diverse range of applications, such as drug delivery, tissue engineering and 'smart' systems. Herein, we review some of the most interesting examples of recent advances and progressive applications of elastin-like recombinamers in biomaterial and nano-engineering sciences in recent years.